2010
DOI: 10.2478/v10009-010-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Body size and reproductive traits of Palaemon elegans Rathke, 1837 (Crustacea, Decapoda), a recent colonizer of the Baltic Sea

Abstract: Palaemon elegans is a species of prawn new (since 2000) to the southern Baltic. The aim of this study was to find out whether there are differences in the sizes of individuals and in the reproductive traits of P. elegans inhabiting different areas of the southern Baltic Sea and to compare the data obtained with existing data for populations from other coastal areas. The present study was carried out in the summers of 2005 and 2007 in three areas differing in their hydrological conditions (primarily in salinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…BilGin & Samsun (2006: see table 7, for review) and Janas & Mańkucka (2010: see table 3, for review) compared increases in the change of egg diameter of marine Palaemonids and found the same pattern recorded in this study. AnDerson (1982) states that an increase of the long axis is caused by growth of embryonic structures in the cephalic-caudal axis.…”
Section: Reproductionsupporting
confidence: 53%
“…BilGin & Samsun (2006: see table 7, for review) and Janas & Mańkucka (2010: see table 3, for review) compared increases in the change of egg diameter of marine Palaemonids and found the same pattern recorded in this study. AnDerson (1982) states that an increase of the long axis is caused by growth of embryonic structures in the cephalic-caudal axis.…”
Section: Reproductionsupporting
confidence: 53%
“…Thirty two of ovigerous females were put into the 30 x 30 x 15 cm aquarium individually to observe the eggs development [4], brackishwater was supplied and the water was exchanged twice a day until hatching [13].…”
Section: Methodsmentioning
confidence: 99%
“…elegans is characterized by open habitats [3], usually in the tidal zones, on sandy bottoms covered with macroalgae, bare sandy sea beds, the brown algae belt and stony bottoms [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Baltic prawn Palaemon adspersus Rathke, 1837 occurs almost in the entire Baltic Sea, including some parts of the Gulf of Bothnia and the Gulf of Finland (Janas et al 2013, Katajisto et al 2013. The rockpool prawn Palaemon elegans Rathke, 1837 was recorded only occasionally in the western Baltic until the 1990s (Köhn & Gosselck 1989), but in the early 21 century, the species colonized the southern and the north-eastern Baltic Sea on a large scale (Janas et al 2004, Grabowski 2006, Janas & Mańkucka 2010, Katajisto et al 2013). This colonization was most probably a result of human introduction (Reuschel et al 2010).…”
Section: Introductionmentioning
confidence: 99%